2009
DOI: 10.14430/arctic365
|View full text |Cite
|
Sign up to set email alerts
|

Oilfield Development and Glaucous Gull (Larus hyperboreus) Distribution and Abundance in Central Alaskan Beaufort Sea Lagoons, 1970–2001

Abstract: ABSTRACT. We evaluated aerial survey data for glaucous gulls (Larus hyperboreus) in central Alaskan Beaufort Sea lagoons near the Prudhoe Bay oilfields during June to September 1978September -2001 for trends in numbers of glaucous gulls, associations with human activity, and confounding relationships with environmental variables. Most glaucous gulls were in barrier island and mainland shoreline habitats, and the total number of gulls per survey ranged from 50 to 1600. Seasonal variation in abundance was appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Glaucous Gulls nest across Alaska's Arctic Coastal Plain; studies have indicated their populations may be more concentrated near coastal villages and areas of industrial development such as Kuparuk and Prudhoe Bay (Noel et al 2006). Other potential predators of ducklings at Kuparuk included Parasitic Jaeger, Common Raven (Corvus corax), and arctic fox (Alopex lagopus).…”
Section: Discussionmentioning
confidence: 99%
“…Glaucous Gulls nest across Alaska's Arctic Coastal Plain; studies have indicated their populations may be more concentrated near coastal villages and areas of industrial development such as Kuparuk and Prudhoe Bay (Noel et al 2006). Other potential predators of ducklings at Kuparuk included Parasitic Jaeger, Common Raven (Corvus corax), and arctic fox (Alopex lagopus).…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive success of glaucous gulls in this area is positively associated with the amount of garbage in the gulls' diets (Weiser and Powell, 2010), so development with an associated increase in garbage availability may cause gull population growth. Unfortunately, historical data on glaucous gull numbers on the ACP are scarce, so it is not clear whether populations have increased in response to past development (Noel et al, 2006). However, there is anecdotal evidence that glaucous gull densities may have increased in developed areas of western and northern Alaska in recent decades (Springer, 1987;USFWS, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is anecdotal evidence that glaucous gull densities may have increased in developed areas of western and northern Alaska in recent decades (Springer, 1987;USFWS, 2003). Moreover, recent aerial surveys have revealed higher concentrations of glaucous gulls near villages and oilfields than in surrounding undeveloped areas (Noel et al, 2006). The cause of this pattern is not clear, but one possibility is that anthropogenic foods support or attract higher densities of gulls than undeveloped areas.…”
Section: Introductionmentioning
confidence: 99%
“…Garbage disposal and other sources of anthropogenic food (lunch sacks, feeding wildlife, etc.) improved drastically since the 1980s and there was no clear trend in abundance of gulls in the lagoons at Prudhoe Bay during the period of oilfield development (1978–2001; Noel et al 2006), directly before our study began. Avian predator numbers within the oilfields have not been monitored systematically since then, and there is no information, other than this study, on whether their numbers decreased when practices were improved, and then increased over the past two decades.…”
Section: Discussionmentioning
confidence: 83%